2016
DOI: 10.1080/19443994.2015.1083483
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of microbial communities in an integrated ultrafiltration–reverse osmosis desalination pilot plant located at the Arabian Gulf

Abstract: This study demonstrated the use of high-throughput sequencing to assess the efficacy of an integrated Ultrafiltration (UF)-Reverse Osmosis (RO) desalination pilot plant located at the Arabian Gulf, and to identify potential microbial-associated problems that may arise in this plant.When integrated into the desalination treatment system, the UF membranes were able to serve as a good pretreatment strategy to delay RO fouling by achieving up to 1.96-log removal of cells from the seawater. Consequently, the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Physical pretreatment is less expensive than traditional chemical pretreatment since no additional chemicals need to be added, this includes the additional costs of the UF membranes [71]. Hollow fiber UF technology has increasingly gained acceptance as a viable alternative for seawater pretreatment [72][73][74]. Reasons for the increasing interest in UF pretreatment over conventional approaches include superior and more consistent filtrate water quality, ability to cope with variable feed water quality, lower plant footprint, and competitive cost [72].…”
Section: Fouling Mitigation Strategies I Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical pretreatment is less expensive than traditional chemical pretreatment since no additional chemicals need to be added, this includes the additional costs of the UF membranes [71]. Hollow fiber UF technology has increasingly gained acceptance as a viable alternative for seawater pretreatment [72][73][74]. Reasons for the increasing interest in UF pretreatment over conventional approaches include superior and more consistent filtrate water quality, ability to cope with variable feed water quality, lower plant footprint, and competitive cost [72].…”
Section: Fouling Mitigation Strategies I Pretreatmentmentioning
confidence: 99%
“…UF membranes with a pore size of 0.02 µm have been the most effective for removing silt, algae, bacteria, and large molecular weight organics [70]. For example, Hong et al [74] demonstrated that the UF pretreatment achieved 1.96-log removal of bacterial cells. The permeate stream must have a turbidity below 0.1 NTU and a 15 min.…”
Section: Fouling Mitigation Strategies I Pretreatmentmentioning
confidence: 99%
“…Metabisulfite is commonly added to neutralize chlorine or other oxidizing biocides in desalination plants in order to protect the integrity of the membranes used. However, excess sulfate can select for SRB, which can produce corrosive hydrogen sulfide that damages membrane integrity [18]. …”
Section: Introductionmentioning
confidence: 99%
“…and Desulfovibrio spp. were identified on fouled ultrafiltration (UF) and RO membranes sampled from a SWRO pilot plant located in the Arabian Gulf (Hong et al, 2016 ). Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…and other sulfate-reducing bacteria (SRB) by depleting oxygen. In addition, SRB and Pseudomonas aeruginosa are able to reduce sulfate and thiosulfate, respectively, to produce hydrogen sulfide, a corrosive and toxic gas (Hong et al, 2016 ). The presence of Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%